EVALUATION OF SOME EXPLICIT SUMMATION FORMULAE FOR TRUNCATED GAUSS FUNCTION AND APPLICATIONS - Qureshi, M. I; Jabee, S; Ahamad, D (TWMS journal of applied and engineering mathematics, 2022)
In this paper, some explicit expressions for truncated Gauss' hypergeometric series 2F1 with argument 2, when one numerator and one denominator parameters are negative integers such as 21 [Please download the PDF to view the mathematical expression] are obtained with the help of Whipple and Vidunas identities respectively. Further, we derive some results as applications of these summation theorems. Keywords: Gauss' hypergeometric function, generalized hypergeometric function, truncated series. AMS Subject Classification: 33C05, 33C20, 44A10.